Curcumin-mediated transcriptional regulation of human N-acetylgalactosamine-α2,6-sialyltransferase which synthesizes sialyl-Tn antigen in HCT116 human colon cancer cells - An, So-Young; Kim, Kyoung-Sook; Cho, Jong-Hyun; Kim, Hee-Do; Kim, Cheorl-Ho; Lee, Young-Choon (Frontiers in Molecular Biosciences, 2022)
Human N-acetylgalactosamine-α2,6-sialyltransferase (hST6GalNAc I) is the major enzyme involved in the biosynthesis of sialyl-Tn antigen (sTn), which is well known to be expressed in more than 80% of human carcinomas and to be correlated with poor prognosis in cancer patients. Athough high expression of hST6GalNAc I gene is associated with the augmented proliferation, migration and invasion in various cancer cells, transcriptional mechanism regulating hST6GalNAc I gene expression remains largely unknown. In this study, we found that hST6GalNAc I gene expression was markedly augmented by curcumin in HCT116 human colon carcinoma cells. To understand the molecular mechanism for the upregulation of hST6GalNAc I gene expression by curcumin in HCT116 cells, we first determined the transcriptional start site of hST6GalNAc I gene by 5'-RACE and cloned the proximal hST6GalNAc I 5'-flanking region spanning about 2 kb by PCR. Functional analysis of the hST6GalNAc I 5′ flanking region of the hST6GalNAc I by the sequential 5’-deletion, transient transfection of reporter gene constructs and luciferase reporter assays showed that -378/-136 region is essential for maximal activation of transcription in response to curcumin in HCT 116 cells. This region includes putative binding sites for transcription factors c-Ets-1, NF-1, GATA-1, ER-α, YY1, and GR-α. ChIP analysis and site-directed mutagenesis demonstrated that estrogen receptor α (ER-α) binding site (nucleotides -248/-238) in this region is crucial for hST6GalNAc I gene transcription in response to curcumin stimulation in HCT116 cells. The transcription activity of hST6GalNAc I gene induced by curcumin in HCT116 cells was strongly inhibited by PKC inhibitor (Gö6983) and ERK inhibitor (U0126). These results suggest that curcumin-induced hST6GalNAc I gene expression in HCT116 cells is modulated through PKC/ERKs signal pathway.